Accurate numerical treatment on a stochastic SIR epidemic model with optimal control strategy - Ghosh, Indranil; Rashid, Muhammad Mahbubur; Ghosh, Pallabi; Mawa, Shukranul; Roy, Rupal; Ahsan, Md Manjurul; Gupta, Kishor Datta (2022)
In this paper, a numerical study has been undertaken on the susceptible-infectedrecovered (SIR) epidemic model that encompasses the mechanisms of the evolution of disease transmission; a prophylactic vaccination strategy in the susceptible populations, depending on the infective individuals. We furnish numerical and graphical simulation combined with explicit series solutions of the proposed model using the New Iterative Method (NIM) and Modified New Iterative Method (MNIM). The analytic-numeric New Iterative Method failed to deliver accurate solution for the large time domain. A new reliable algorithm based on NIM, the coupling of the Laplace transforms, and the New Iterative method is called Modified New Iterative Method (MNIM) which is presented to enhance the validity domain of NIM techniques. The convergence analysis of the MNIM has also been illustrated. The simulation results show that the vaccination strategy can slow down the spread of the epidemic rapidly. Numerical results illustrate the excellent performance of the MNIM and show that the modified method is much more accurate than the NIM.